2004
DOI: 10.1002/jso.20140
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the age factor in the thyroid cancer: Statistical analysis

Abstract: Statistical analysis shows that the greater biological aggressiveness of the neoplasm in elderly patients worsens the prognosis, although an age exceeding 70 years itself represents an unfavourable prognostic factor; total thyroidectomy does not present any counter-indications in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 25 publications
3
14
0
1
Order By: Relevance
“…Although a relation between the initial treatment failure and recurrent disease was suggested, this could not be established in the present study, as differences in failure rates between patients with and without recurrent DTC were not statistically significant. This finding is in agreement with the data published by Falvo et al (13).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Although a relation between the initial treatment failure and recurrent disease was suggested, this could not be established in the present study, as differences in failure rates between patients with and without recurrent DTC were not statistically significant. This finding is in agreement with the data published by Falvo et al (13).…”
Section: Discussionsupporting
confidence: 94%
“…In this respect, we observed not only a significant difference between patients with M0 disease (42.6 years) and those with M1 disease (61.9 years; PZ0.001), but also between M0 tumor stage patients with (50.7 years) and without (41.5 years; PZ0.013) recurrent disease. Falvo et al (13) performed a study on biologically aggressiveness of DTC in elderly patients, in which an age exceeding 70 years represented the most unfavorable prognosis. Haq et al (17) reported a comparable age of 70 years and older in relation to a poor outcome.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 In papillary carcinoma, 63 of 123 cases showed high expression of delta Np73, but its expression level was significantly decreased in cases showing larger tumour, advanced patient age, massive extrathyroid extension and the presence of clinically apparent node metastasis. Since these parameters have been recognised as prognostic factors of patients with papillary carcinoma, [11][12][13][14] it is suggested that the delta Np73 expression level is even higher in patients with mild characteristics and with favorable prognosis. Furthermore, 70% of microcarcinomas, most of which grow slowly or not at all, 10 expressed a high level of delta Np73, indicating that this protein is not likely to significantly contribute to cell proliferation.…”
Section: Discussionmentioning
confidence: 98%
“…10 However, cases demonstrating aggressive features or risk factors such as advanced patient age, large tumour, massive extrathyroidal extension, and clinically apparent nodal metastasis (metastatic node, which is palpable or detected by preoperative ultrasonography) can show a dire prognosis. [11][12][13][14] Furthermore, once papillary or follicular carcinomas dedifferentiate, they are called anaplastic (undifferentiated) carcinoma and display extremely rapid growth with a dire prognosis. 15 To date, there is one manuscript reporting a high level of delta Np73 expression in thyroid carcinoma, 16 but the number of cases in this series is small for evaluating the role of this transcript in the progression of this carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Bioquímicamen-te, el diagnóstico se basa en la detección de cifras elevadas de calcitonina sérica 3,8 . La presencia de metástasis a linfonodos regionales es habitual, encontrándose en 45% de los pacientes al momento del diagnóstico 9 , y es uno de los factores predictores de resultado adverso, junto con la extensión del tumor primario, edad avanzada, metástasis a distancia y el tiempo de duplicación de calcitonina y del antígeno carcinoembrionario en el post operatorio 4,[10][11][12] . La cirugía es el único tratamiento curativo 10 .…”
unclassified